Advanced light-tolerant microalgae-nitrifying bacteria consortia for stable ammonia removal under strong light irradiation using light-shielding hydrogel. (June 2022) - Nishi, Kento; Akizuki, Shinichi; Toda, Tatsuki; Matsuyama, Tatsushi; Ida, Junichi
Abstract: The consortium of microalgae and nitrifying bacteria has attracted attention owing to its advantages, such as energy- and cost-efficiency in terms of using only light irradiation without aeration. However, high light intensity can easily cause photoinhibition of nitrifying bacteria, resulting in process breakdown of the consortium. This challenge limits its practical application in outdoor environment. In a previous study, we developed a "light-shielding hydrogel" which entrapped nitrifying bacteria in carbon black-added alginate hydrogel beads and confirmed its effectiveness of protecting the nitrifying bacteria from intense light up to 1600 μmol photons m −2 s −1 . However, the applicability of the light-shielding hydrogel to microalgae–nitrifying bacteria consortia under strong light irradiation has not yet been clarified. In this study, we aimed to establish consortia of Chlorella sorokiniana and nitrifying bacteria immobilised in light-shielding hydrogel and evaluate their nitrification performance under strong light. Three nitrifying bacteria conditions were used: light-shielding hydrogel, hydrogel containing only nitrifying bacteria without carbon black ('hydrogel'), and dispersed nitrifier without immobilisation ('dispersion') as a control. At 1600 μmol photons m −2 s −1, the dispersion afforded a significant decrease in nitrification activity and subsequent process breakdown. In contrast, light-shielding hydrogel achieved complete nitrification without nitrite accumulation and had nitrification rates of approximately nine and two times higher than those for the dispersion and hydrogel conditions, respectively. Based on the overall evaluation, a possible sequence of process breakdown under strong light was also proposed. This study demonstrated for the first time that the light-shielding hydrogel/consortia combination had potential for applications, which require mitigation of photoinhibition under strong light irradiation. Further, it is expected that the proposed method will contribute to realise the practical application of microalgae–nitrifying bacteria consortia in various countries that experience high sunlight intensity due to their location in the sunbelt areas. Graphical abstract: Image 1 Highlights: F06C Established advanced light-tolerant consortia of microalgae and nitrifying bacteria. F06C Ammonia removal efficiency under strong light of 1600 μmol m −2 s −1 was 74%. F06C 9 times higher nitrification rates at 1600 μmol m −2 s −1 against control. F06C Possible mechanism of process failure triggered by strong light was proposed. F06C Demonstrated potential of proposed method for practical application in outdoor.